KEPERCAYAAN MISTISME KONTEN YOUTUBE (ANALISIS RESEPSI MAHASISWA SURABAYA PADA KONTEN SARA WIJAYANTO) (The Commercium, 2023)
Abstract Youtube content as a form of new media has a role as media that describes social reality. The audience as an active audience plays a role as a result of interpreting a media message.The content of Sara's Mystery Diary is a short video with lots of mystical scenes about spirits. The scene will produce different meanings for each individual. With this problem, the research discussed the content of "Dutch House in the Sugar Factory and Bank of the Unseen” in the meaning of Surabaya students' belief in mystical things. This study uses the reception analysis method involving four informants who are members of the Saraddicts.Surabaya instagram account followers who focus on two content objects in each supernatural mystical scene. The results of this study are three categories according to Dominant, Negotiation and Opposition. Keywords : Reception Analysis, Content mysticism sara wijayanto